Penempatan Static Var Compensator (SVC) Untuk Perbaikan Profil Tegangan Pada Jaringan Transmisi - Nurul Whusto; Edy Ervianto; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
A good electric power system must have a voltage value that does not exceed the tolerance limit, also a small power loss. The tolerance limit allowed for the value of the voltage is ± 5%of the nominal value. The use of Static Var Compensator (SVC) is an attempt to overcome the problem of loss of transmission power and voltage drop due to the addition of electricalloads. In this study, SVC placement was carried out on the IEEE 14 bus transmission network using an electrical power system analysis software. Simulation results show a decrease inactive power losses from 68.5 MW to 43,7 MW and reactive power losses from 256.4 MVAR to 160,8 MVAR.Keywords – IEEE 14 Bus, Power losses, Static VAR Compensator